Culture Conditions for In Vitro Maturation of Abattoir Derived Oocytes of Native Zebu Cows of Bangladesh - SM Niyaz Morshed; Mohammad Musharraf Uddin Bhuiyan; Mohammad Moshiur Rahman; Joydev Kumer Singha; Nasrin Sultana Juyena (The Korean Society of Animal Reproduction and Biotechnology, 2014)
The objectives of the study were to determine an effective culture dish, culture duration and protein supplementation in medium for in vitro maturation (IVM) of oocytes of native zebu cows in Bangladesh. The ovaries of cows were collected from local slaughterhouse followed by aspiration of follicular fluid. The cumulus-oocyte-complexes (COCs) with more than 3 compact cumulus cell layers were cultured in tissue culture medium (TCM) 199 for maturation. The maturation of oocytes was determined by observing polar body under microscope. To determine an effective culture dish, 130 COCs derived from 48 ovaries in a well of 4-well dish and 102 COCs derived from 36 ovaries in drops covered with mineral oil within 35 mm petri dish were cultured for 24 hours. The rate of maturation of oocytes did not vary between 4-well dish (51.3 ± 15.0 %) and drops in petri dish (52.4 ± 11.6 %). To determine the effective culture duration, 185 COCs derived from 62 ovaries were cultured in drops for 18, 21, 24 and 27 hours. The rate of maturation of occytes ranged from 51.9 ± 9.4 % (18 hours) to 59.0 ± 17.1 % (27 hours) and the difference in maturation rate among different culture durations was not significant (P>0.05). To determine an effective protein supplementation, 63 oocytes from 19 ovaries were cultured separately in TCM 199 supplemented with either fetal bovine serum (FBS) or bovine serum albumin (BSA). The rate of maturation was significantly (P<0.01) higher in medium supplemented with FBS (55.63 ± 16.19 %) than that of BSA (14.82 ± 9.36 %). In conclusion, COCs of native zebu cows can be cultured for IVM either in 4-well culture dish or droplets in petri dish for 18 to 27 hours in medium supplemented with FBS.